Mobile Learning Usage and Preferences of Vocational Secondary School Students: The cases of Austria, the Czech Republic, and Germany - Antun Biloš; Davorin Turkalj; Ivan Kelić (Naše gospodarstvo/Our economy, 2017)
The purpose of this paper is to determine the current status of mobile device usage and mobile learning adoption in vocational education and training (VET) secondary schools in three European Union countries (Austria, the Czech Republic, and Germany). The research focused on exploring students’ mobile device usage habits, their attitudes toward education in the context of mobile application support, and preferences regarding mobile learning features. The research confirmed a high level of mobile device usage among secondary school students on a daily basis; smartphones and laptops were the most commonly used devices. The vast majority of participants perceived themselves to be advanced mobile device users, but reported a deficit of ICT-assisted mobile learning experience. However, the majority of respondents with prior ICT-assisted education experience described it as a positive or very positive experience. In addition, study participants tended to agree that mobile learning will play a significant role in education in the future. The paper also explored the reported differences among the students in the three countries and suggested several implications for understanding students’ views of mobile learning. The findings provide insights into possibilities of m-learning implementation while creating a framework for m-learning application development in the VET secondary school environment.